Challenges and support service preferences of informal caregivers of people with systemic sclerosis: a cross-sectional survey. Issue 16 (30th July 2020) - Rice, Danielle B.; Cañedo-Ayala, Mara; Carboni-Jiménez, Andrea; Carrier, Marie-Eve; Cumin, Julie; Malcarne, Vanessa L.; Hagedoorn, Mariët; Thombs, Brett D.; ,
Abstract: Purpose: To evaluate the importance of different challenges experienced by informal caregivers to persons with systemic sclerosis (SSc) and identify priorities for support services that could be developed. Materials and Methods: Caregivers of people with SSc from three continents completed an online questionnaire to rate the importance of possible caregiver challenges and likelihood of using different forms of support services. Importance of challenges and likelihood of using support services were rated from 1 (not important; not likely to use) to 4 (very important; very likely to use). Results: Two hundred and two informal caregivers completed the survey (79 women, 123 men). Mean age was 58 years (standard deviation = 13). The most important challenges were related to supporting the care recipient with emotional difficulties and physical discomfort. Caregivers indicated that they would be more likely to use support services that involved online or hard-copy information resources, including those provided soon after diagnosis, compared to support that involved interacting with others. Conclusions: Supporting the care recipient in managing emotional difficulties and physical discomfort were important challenges among caregivers. Interventions delivered through hardcopy or online resources, including those delivered soon after the care recipient's diagnosis, were rated as being most likely to be used by caregivers. Implications for rehabilitation: Many caregivers for individuals with systemic sclerosis report struggling to support their care recipient with emotional difficulties and physical discomfort. Rehabilitation professionals can aid in the development of support services that caregivers have identified as being likely to use and can refer caregivers to resources that they have identified as being helpful, such as educational information about the disease. The development of support services should focus on aspects of caring that caregivers found most challenging and be delivered in a format that considers caregiver preferences.